Crista Terminalis, Musculi Pectinati, and Taenia Sagittalis: Anatomical Observations and Applied Significance. (13th August 2013) - Siddiqui, Abu Ubaida; Daimi, Syed Rehan Hafiz; Gandhi, Kusum Rajendra; Siddiqui, Abu Talha; Trivedi, Soumitra; Sinha, Manisha B.; Rathore, Mrithunjay
Abstract : Background . The complex architecture of the right atrium, crista terminalis (CT), and the musculi pectinati (MP) poses enormous challenges in electrophysiology and cardiac conduction. Few studies have been undertaken to substantiate the gross features of MP, in relation to the CT, but there is still scarcity of data regarding this. We tried to reinvestigate the gross arrangement of muscle bundles in the right atrium. Methods . Utilizing 151 human hearts and orientation of MP and its variations and relationship to the CT were investigated along with taenia sagittalis (TS). Patterns of MP were grouped in 6 categories and TS under three groups. Result . A plethora of variations were observed. Analysis of all the specimen revealed that 68 samples (45%) were of type 1 category and 27 (18%) fell into type 2 category. Prominent muscular columns were reported in 12 samples (8%). 83 samples (55%) presented with a single trunk of TS. Multiple trunks of TS were reported in 38 samples (25%). Conclusion . Samples with type 6 MP and type B/type C TS, which have a more complex arrangement of fibers, have a tendency to be damaged during cardiac catheterization. Nonetheless, the area as a whole is extremely significant considering the pragmatic application during various cardiac interventions.